AB0625 Survival and Prognostic Factors in Patients with Connective Tissue Disease-Associated Pulmonary Arterial Hypertension: Results from A Korean Nationwide Registry. (10th June 2014) - Kang, K.Y.; Jeon, C.H.; Choi, S.J.; Yoon, B.Y.; Choi, C.-B.; Lee, C.H.; Suh, C.-H.S.; Lee, C.W.; Cho, C.S.C.; Nam, E.J.; Koh, E.-M.; Kim, H.-Y.; et al.
Abstract : Background: Pulmonary arterial hypertension (PAH) is a major cause of mortality in connective tissue disease (CTD). Objectives: The survival rates and mortality-predictive factors of a nationwide registry of Korean patients with CTD-PAH were determined. Methods: Patients with CTD-PAH were enrolled between April 2008 and December 2012. Hemodynamic parameters and clinical data (WHO-functional class [FC], organ involvement, laboratory tests, and treatment agents) were recorded. Survival rates were calculated by using the Kaplan–Meier method. Mortality-associated factors were examined by Cox proportional hazards regression analysis. Results: In total, 174 incident PAH cases (61 with systemic lupus erythematosus, 50 with systemic sclerosis, 10 with mixed CTD, 22 with rheumatoid arthritis [RA], and 31 with other CTDs) were diagnosed by right heart catheterisation or Doppler echocardiography. Of these, 25 (14%) died during the 3.8±2.7 year follow-up period after PAH diagnosis. The 1 and 3 year survival rates were 90.7% and 87.3%, respectively. Compared to the other CTD-PAHs, RA-PAH had the lowest survival rates (56% 3 year survival; p =0.022). Multiple regression analysis revealed that low DLCO, pleural effusion, and diabetes mellitus were poor prognostic factors ( p =0.008, 0.04, and 0.009, respectively). Anti-UI-RNP antibody positivity was protective ( p =0.022). In patients with WHO-FC III/IV, patients who received vasodilators had lower mortality than those who did not ( p =0.038). Conclusions: In Korean patients with CTD-PAH, the 3 year survival rate was 87%. Low DLCO, pleural effusion, and DM were independent poor prognostic factors. Anti-UI-RNP antibody was protective. Prompt PAH-specific vasodilator therapy may improve the survival of patients with severe CTD-PAH. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1271